DIGITALISASI SISTEM PEMBAYARAN DAN RISIKO HUKUM AI DALAM DETEKSI FRAUD: KEPASTIAN HUKUM BAGI PELAKU USAHA DAN KONSUMEN DALAM EKONOMI FINANSIAL TEKNOLOGI - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
The digitisation of payment systems has been a fundamental catalyst in the transformation of Indonesia’s fintech economy, shifting the transaction paradigm from cash-based transactions towards a nationally integrated cashless ecosystem (cashless society). However, the accelerated adoption of this technology presents complex legal risks that have not yet been fully accommodated within the regulatory framework, particularly regarding the use of artificial intelligence (AI) in fraud detection, which has the potential to cause algorithmic bias, detection errors (false positives/negatives), and uncertainty regarding legal liability. This study aims to analyse two main dimensions: first, the digital transformation of payment systems within the fintech economy and its legal implications; second, the legal risks of using AI in fraud detection and its impact on legal certainty for businesses and consumers. The research method employed is normative legal research using a literature review approach (library research), focusing on the analysis of primary, secondary, and tertiary legal materials. The research findings indicate that the absence of specific regulations regarding AI liability creates a legal grey area that is detrimental to both businesses and consumers, hinders innovation, and has the potential to erode public trust in the fintech ecosystem. Legal certainty can only be achieved through regulatory harmonisation that adopts the principle of risk-proportionate oversight, mandatory periodic algorithm audits, the implementation of explainable AI (XAI) standards, and rapid compensation mechanisms for victims of detection errors. This study recommends strengthening the legal framework for AI in the fintech sector through collaboration between regulators, the adoption of international best practices, and the improvement of public digital literacy to ensure that the digital transformation of payment systems proceeds in a sustainable, fair, and beneficial manner for all stakeholders.